2015
DOI: 10.12973/eurasia.2015.1339a
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Fostering Higher Levels of Geometric Thinking

Abstract: Pierre M. Van Hiele created five levels of geometric thinking. We decided to identify the level of geometric thinking in the students in Slovenia, aged 9 to 11 years. The majority of students (60.7 %) are at the transition between the zero (visual) level and the first (descriptive) level of geometric thinking. Nearly a third (31.7%) of students is at the first level whereas 4.3 % of students are at the zero level. Only 1.4 % of students reached the second level of geometric thinking. Students had the most diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
(13 reference statements)
0
10
0
1
Order By: Relevance
“…In addition to analyzing differences in selfefficiency in geometry according to variables: sex, grade, educational achievement, and used the Van Hiele scale in geometry thinking, as well as a test of self-efficacy, and the results of the study showed a vulnerable correlation between self-efficacy and geometric thinking, as the results of the study showed variations in self-efficacy in accordance to the gender, class, achievement. Skrbec & Cadez (2015) conducted a study to perceive the levels of geometric thinking among students in the primary stage in Slovenia; the study's results confirmed that there had been 4% of students at the zero level, 61% between the zero and first level, and 32% at the first level, and the 2d level only 1% of students. The results of the study also confirmed the weakness of students in the preference of geometry language.…”
Section: Introductionmentioning
confidence: 85%
“…In addition to analyzing differences in selfefficiency in geometry according to variables: sex, grade, educational achievement, and used the Van Hiele scale in geometry thinking, as well as a test of self-efficacy, and the results of the study showed a vulnerable correlation between self-efficacy and geometric thinking, as the results of the study showed variations in self-efficacy in accordance to the gender, class, achievement. Skrbec & Cadez (2015) conducted a study to perceive the levels of geometric thinking among students in the primary stage in Slovenia; the study's results confirmed that there had been 4% of students at the zero level, 61% between the zero and first level, and 32% at the first level, and the 2d level only 1% of students. The results of the study also confirmed the weakness of students in the preference of geometry language.…”
Section: Introductionmentioning
confidence: 85%
“…This is because the ability of technology is easy to manipulate and manage, making it easier for students to understand a concept compared to conventional learning [50]. [41] as well as Škrbec and Čadež [40] used varied materials and concrete experiences in developing students' geometric thinking. However, Markopoulos, et al [41] found that not all students achieved an advanced level of thinking.…”
Section: Methodsmentioning
confidence: 99%
“…In a study to identify the levels of geometric thinking among students aged 9-11 years in Slovenia, the results of the study showed that 4% of students in the zero level, 61% between zero and first, and 32% In the first level, and the second level reached only 1% of students, and the results of the study showed the weakness of students in the choice of geometric language [13].…”
Section: Introductionmentioning
confidence: 96%